Physiological assessment of Common Carotid Artery End Diastolic Velocity, a hemodynamic parameter, with future risk for the development of cerebrovascular stroke (Indian Journal of Applied-Basic Medical Sciences, 2020)
Aim: Assessment of Common carotid artery end diastolic velocity , a hemodynamic parameter, with the future risk for development of Cerebrovascular stroke . In order to assess common carotid artery end diastolic velocity , we have evaluated age, BMI, W/H , blood pressure , lipid profile and HbA1c in CV Stroke and control subjects. Material method: The present study was conducted on 30 CV Stroke patients(Group A) and 30 non stroke hypertensive and diabetic patients (Group B) . CCA End diastolic velocity was assessed in each group by Doppler ultrasound machine. BMI and W/H was measured according to WHO protocol. Blood pressure was measured by sphygmomanometer. Lipid profile and HbA1c was done by autoanalyser machine . Result : CCA End diastolic velocity in Group A and group B was found to be 10.49±6.02 & 17.70±4.18 and 12.59±3.47 & 21.47±5.21 in right and left side respectively. The data was highly significant (p
Keywords: CCA EDV; CV stroke; HbA1c; HDL; LDL; Total cholesterol; triglyceride